Interictal Abnormalities of Neuromagnetic Gamma Oscillations in Migraine Following Negative Emotional Stimulation - Wu, Ting; Fan, Jie; Chen, Yueqiu; Xiang, Jing; Zhu, Donglin; Zhang, Junpeng; Shi, Jingping; Jiang, Tianzi (Frontiers in Behavioral Neuroscience, 2018)
Here we aimed to investigate brain activity in migraineurs in response to emotional stimulation. Magnetoencephalography(MEG) was used to examine 20 patients with episodic migraine (EM group), 15 patients with chronic migraine (CM group), and 35 healthy participants (control group).Neuromagnetic brain activity waselicited by emotional stimulation using photographs of facial expressions.We analyzed the latency and amplitude of M100 and M170 components and used Morlet wavelet and beamformers to analyze the spectral and spatial signatures of MEG signals in gamma band (30-100Hz).We found thatthe timing and frequency of MEG activity differed across the three groups in response negative emotional stimuli. First, peak M170 amplitude was significantly lower in the CM group than in the control group. Second, compared with the control group, the average spectral power was significantly lower in the EM group at M170 and in the CM group at M100 and M170.Third, the average spectral powers of the M100 and M170 in the CM group were negatively correlated with either HAM-D scores or migraine attack frequency. no significant differences across groups was found for positive or neutral emotional stimuli. Furthermore, after negative emotional stimuli, the MEG source analysis demonstrated that the CM group showed a significantly higher percentage of amygdala activation than the control group for M100 and M170.Thus, during headache free phases, migraineurshave abnormal brain activity in the gamma band in response to negative emotional stimuli.